2021
DOI: 10.1164/rccm.202004-1006oc
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction and Hemodynamics with Initial Combination Therapy in Pulmonary Arterial Hypertension

Abstract: Rationale: An initial oral combination of drugs is being recommended in pulmonary arterial hypertension (PAH), but the effects of this approach on risk reduction and pulmonary vascular resistance (PVR) are not known.Objectives: To test the hypothesis that a low-risk status would be determined by the reduction of PVR in patients with PAH treated upfront with a combination of oral drugs. Methods:The study enrolled 181 treatment-naive patients with PAH (81% idiopathic) with a follow-up right heart catheterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 30 publications
3
45
0
1
Order By: Relevance
“…Double oral therapy showed an additional effect on PVR reduction compared with oral monotherapy, with a reduction ranging between 30 and 60% [19,[62][63][64]. Such modest improvement in PVR, usually <50% for the majority of patients treated with double oral therapy, is associated with a non-significative improvement in echo-determined right heart sizes, while weakly associated with improvement in RV systolic function [60].…”
Section: Impact Of Therapeutic Strategies On Echocardiographic-derivementioning
confidence: 98%
See 1 more Smart Citation
“…Double oral therapy showed an additional effect on PVR reduction compared with oral monotherapy, with a reduction ranging between 30 and 60% [19,[62][63][64]. Such modest improvement in PVR, usually <50% for the majority of patients treated with double oral therapy, is associated with a non-significative improvement in echo-determined right heart sizes, while weakly associated with improvement in RV systolic function [60].…”
Section: Impact Of Therapeutic Strategies On Echocardiographic-derivementioning
confidence: 98%
“…Such RHRR is associated with excellent long-term survival and quality of life. However, studies showed that monotherapy or stepwise additions to initial monotherapy allow these results in a small percentage of patients (18%) [56,61,63,67]. On the other hand, an upfront combination therapy, including parenteral prostacyclins, is associated with RHRR in a greater proportion of patients than other treatment strategies as a function of PVR reduction.…”
Section: Impact Of Therapeutic Strategies On Echocardiographic-derivementioning
confidence: 99%
“…We thank Weatherald and colleagues for their supportive comments, and pleasant reminiscence of French cuisine, on our recent report on risk reduction and hemodynamics after initial dual combination of therapies in pulmonary arterial hypertension ( 1 ). We fully agree on the importance of pulmonary vascular resistance combined with imaging of the right heart, as there may be dissociation ( 2 ), although this is unlikely when pulmonary vascular resistance decreases by more than 50–60% ( 3 ).…”
mentioning
confidence: 99%
“…We read the recent manuscript by Badagliacca and colleagues with great interest ( 1 ). In this Italian multicenter retrospective cohort of 181 treatment-naive patients with pulmonary arterial hypertension (PAH), they evaluated the relationship between change in pulmonary vascular resistance (PVR) following initiation of dual oral combination therapy and two widely used approaches for multidimensional risk assessment ( 2 , 3 ).…”
mentioning
confidence: 99%
“…Lastly, Badagliacca and colleagues highlight the near certainty of treatment failure with dual oral combination therapy in high-risk patients, as none improved to low risk in their study ( 1 ). This reinforces the notion of initial triple combination therapy, including a parenteral prostacyclin for high-risk patients, consistent with previous observational studies ( 9 , 10 ) and the treatment algorithm proposed in the sixth World Symposium on Pulmonary Hypertension ( 11 ).…”
mentioning
confidence: 99%